The Influence of Racial Minorities and Ethnic Heterogeneity in the Estimation of Homicide Rates in the Northeast Region of Brazil: Implications for Social Disorganization Theory in the Global South - Da Silva, Carlos Fabricio Assunção (Homicide studies, 2024)
Using social disorganization theory, the present study considers the concentration of racial minorities and the degree of ethnic heterogeneity to provide an estimation of homicide rates in the Northeast region of Brazil. Three hypotheses were considered: (1) there is a positive association between homicides and ethnic heterogeneity and black/indigenous populations, (2) the magnitude of ethnic heterogeneity is greater than race/minority groups on homicides, and (3) metropolitan regions will be associated with an increase in homicides. Through spatial modelling techniques, results indicate the plausibility of first and third hypotheses. Implications for homicide prevention and social disorganization theory in global south are discussed.